Proposed Red Mobile Library: Alternative Information for Rural Communities in Costa Rica - Guevara Medina, Licda. Elizabeth (2015)
This research analyzes the services provided by the mobile library of SINABI / Public Libraries in rural communities of Costa Rica visited during the year 2009/2010 depending on the sample selected for the presentation of a proposal for Mobile Libraries Network Costa Rica